What Can Chess Teach Students about Career Exploration? Evidence from Group Work - May Trianadya; Devi Permatasari; Laily Tiarani Soejanto (Jurusan Bimbingan dan Konseling, 2026)
Career exploration understanding is a crucial foundation for students in planning their vocational future. This study aims to test the effectiveness of group guidance interventions through chess game techniques in increasing students' career exploration understanding. Using a One Group Pretest- Posttest design, the study involved 10 grade X students of SMA Kristen Petra Malang as subjects. The results of statistical analysis using the Paired Samples T-Test showed a significance value of 0.009 (p < 0.05), which indicates that the use of chess game techniques is significantly effective in helping students understand their potential and devise career plan strategies.